Cases of the End of Parliamentary Interrogation in the Constitution of the Republic of Iraq for the Year 2005 (Comparative Study) - Mohammed Hameed Al-Shajlawe (Indonesian Journal Publisher, 2025)
In the interim period, ie the period between the submission of the motion and discussed in the parliament, challenged opposed held its impact on the events, and ends pursued procedural. Shall be transferred without reaching its destination and this casual but that leads to recover or fall. Perhaps it is worth mentioning that the rules governing these exhibitors representing the general rules applicable to other means of media and parliamentary control on the work of the government or one of its members Calcaal Parliamentary with minor variations required by the subjective nature. Thus, the questioning ends the Bostrdadeh by the introduction unless adopted by another member or by the left and the downfall ends and have it in certain cases Kazhoal recipe introduction or demise described from the face of him or it may be the end of the duration of the legislative parliament